Thought suppression in patients with bipolar disorder. - Miklowitz, D; Alatiq, Y; Geddes, J; Goodwin, G; Williams, J (2010)
Suppression of negative thoughts has been observed under experimental conditions among patients with major depressive disorder (MDD) but has never been examined among patients with bipolar disorder (BD). Patients with BD (n = 36), patients with MDD (n = 20), and healthy controls (n = 20) completed a task that required unscrambling 6-word strings into 5-word sentences, leaving out 1 word. The extra word allowed the sentences to be completed in a negative, neutral, or "hyperpositive" (manic/goal-oriented) way. Participants completed the sentences under conditions of cognitive load (rehearsing a 6-digit number), reward (a bell tone), load and reward, or neither load nor reward. We hypothesized that patients with BD would engage in more active suppression of negative and hyperpositive thoughts than would controls, as revealed by their unscrambling more word strings into negative or hyperpositive sentences. Under conditions of load or reward and in the absence of either load or reward, patients with BD unscrambled more negative sentences than did controls. Under conditions of reward, patients with BD unscrambled more negative sentences than did patients with MDD. Patients with BD also reported more use of negative thought suppression than did controls. These group differences in negative biases were no longer significant when current mood states were controlled. Finally, the groups did not differ in the proportion of hyperpositive sentence completions in any condition. Thought suppression may provide a critical locus for psychological interventions in BD.